Laparoscopic Orchiopexy for the Nonpalpable Testis : 3 Years Experience (TAJ: Journal of Teachers Association, 2018)
We evaluated the safety and efficacy of laparoscopic orchiopexy to manage a nonpalpable intra-abdominal testis and studied the outcomes. We report our 3 years experience.Patients and methods Laparoscopic Orchiopexy was performed on 28 children (32 testicular units) for non-palpable intra-abdominal testis between 2010 and 2012. We retrospectively reviewed the medical records. The mean age was 3.4 years (range, 2.5 -11 years). Of the 28 patients, 18 (64.28 %) were on the right, 6 (21.44%) were on the left and 4 (14.28%) of bilateral. The mean follow-up period was 14.8 months (range, 3-36 months). Testicular viability and orchiopexed positioning were evaluated within 1 month and beyond 3 months.Results  Thirty one testes were descended successfully by laparoscopy. The average operative time was 41.5 ± 3.8 min. Primary laparoscopic orchiopexy done in 26 testes.Three of unilateral and 2 of bilateral testicular units underwent one -stage Fowler-Stephens Orchiopexy. One patient needs laparoscopic orchiectomy. At follow-up (mean 14.8 months), one testis atrophied and need orchiectomy. Testicular survival rate was 96.77% (30/31) and all of the testes maintained an adequate size. Twenty six (86.66%) are in an acceptable scrotal position and 4 testes (13.33%) are mid to high in the scrotum without atrophy. There was no recurrent inguinal hernia.Conclusions  Laparoscopic orchiopexy is successful for a nonpalpable intra-abdominal testis with a high testicular survival rate. The low incidence of complications and high success rate underscore the feasibility of this procedure. It is our procedure of choice for the treatment of nonpalpable testis.TAJ 2011; 24(2): 70-75